3-D Reconstruction of Rock Samples via Structure-From-Motion for Virtual Reality Applications: A Methodological Proposal - Inocencio, Leonardo Campos; Veronez, Maurício Roberto; da Silveira, Luiz Gonzaga; Tognoli, Francisco Manoel Wohnrath [UNESP]; de Souza, Laís Vieira; Bonato, Juliano; Diniz, Jaqueline Lopes (My University, 2023)
This article presents a methodological proposal for the three-dimensional reconstruction of rock samples via structure-from-motion. The presented methodological steps aimed to provide a reproducible workflow to create virtual rock samples to be applied in virtual applications. The proposed methodology works as a how-to guide as well as a preemptive troubleshooting guide for the complete process. Four geologists with different scholar levels volunteered to test this methodological proposal, applying it to three rock samples as the methodology steps were provided in an inverse-proportional manner to the graduate level. When analyzing the results of the performed reconstructions, all analyzed elements presented a proportional reduction due to the lack of information provided. An initial questionnaire was applied to verify the difficulties encountered, and subsequently, all volunteers received the complete methodology. In the second reconstruction, the results were equivalent to those obtained initially with the complete methodology. A technology acceptance model questionnaire was applied to determine the perception of utility and ease of use of the presented methodology. In both cases the results presented themselves in a positive way, indicating that the methodology was able to solve the problems found simply and objectively through a repeatable workflow.
Keywords: geological samples database; structure-from-motion; virtual reality